HUBUNGAN PERAN DOSEN PEMBIMBING DENGAN KECEMASAN MAHASISWA DALAM MENGHADAPI TUGAS AKHIR SKRIPSI DI FAKULTAS KEPERAWATAN UNIVERSITAS PEMBANGUNAN INDONESIA MANADO - Singal, Fabiola (Journal Of Community & Emergency, 2024)
The biggest demand of students is that during the final semester stage students must complete their final project. Problems that often arise are students having difficulty determining titles, finding references difficult, lacking supporting data, unresolved administration, limited research time and other problems. The capital for carrying out the character learning process in tertiary institutions involves the role of a lecturer. The aim of the study was to determine the relationship between the role of the supervising lecturer and student anxiety in facing the final thesis assignment at the Faculty of Nursing, Manado Indonesia Development University. This type of research uses quantitative methods using a cross sectional study approach, the sample in this study uses a purposive sampling technique, the number of samples is 45 respondents. Based on the results of the study, it was found that the results of the active supervisor role test with severe anxiety were 24 (53.3%), active with mild anxiety 5 (11.1%), active with moderate anxiety 7 (15.6%), supervisor role test less active with severe anxiety 4 (8.9%), less active with mild anxiety 2 (4.4%), less active with moderate anxiety 3 (6.2%). The results of statistical tests using the Spearman test obtained a p-value = 0.043 which is less than the value α = 0.05, meaning that H0 is rejected. This study concludes that there is a relationship between the role of supervisors and student anxiety in facing the final thesis assignment at the Faculty of Nursing, Manado Indonesia Development University. Hopefully students can be motivated that thesis is an educational mandate that must be completed properly and in a timely manner.